THE ROLE OF GOVERNMENT APPARATUS (DEVOTION) ON DEVELOPMENT OF BUREAUCRACY IN PUBLIC POLICY PERSPECTIVES IN THE INDUSTRIAL REVOLUTION 4.0 ERA (R & D Study In Rancasari Riung Bandung District, Bandung City, West Java) - Ade Tutty R. Rosa (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2019)
ABSTRACT Problems related to public services include uncertainty over time, costs and ways of providing services to the community making poor service quality. The role of the Camat in the region is very important in terms of public services. The research focus is the Rancasari Riung sub-district of Bandung which requires synergy, measurable steps, coordinated to follow up on programmed problems that have not been effective. It is necessary to improve the ability of the government to be competent in providing services to the community and accepted in the industry, it requires the development of public policy bureaucracy and performance technology capacity. This study aims to improve the performance of government officials, especially the role of the Camat, to influence bureaucratic policy in the perspective of public policy, improve the ability of public service apparatus performance, create quality government, be able to play a role in the disruption and industrial revolution 4.0. Qualitative descriptive research method. Research results The role of Camat in the sub-district that was used as the focus of research in several aspects studied had not all had very good categories, especially related to quality and quality public services. Keywords: critical policy analysis, bureaucratic development, industrial revolution 4.0